PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PARIWISATA KABUPATEN SAMOSIR - Sihotang, Ronael Jon Feriando; Raya Panjaitan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Employee performance is a critical factor in achieving organizational goals, particularly in government institutions such as the Samosir Regency Tourism Office. This study aims to analyze the influence of organizational culture and work discipline on employee performance at the Samosir Regency Tourism Office. The research employs an associative quantitative approach, with a population of all 68 employees of the office, taken as a census sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that both organizational culture and work discipline partially and simultaneously have a positive and significant effect on employee performance. The coefficient of determination (R²) of 0.716 indicates that the two independent variables contribute 71.6% to the variation in employee performance. The practical implication of this research is the need for the Tourism Office to strengthen an organizational culture oriented towards innovation, results, and teamwork, as well as to improve work discipline through rule enforcement, effective supervision, and a clear system of rewards and sanctions. These findings can serve as a reference for improving human resource management and enhancing public services in the tourism sector.